Hearing loss, gait and balance impairments and falls among individuals with sub-acute stroke: A comparative cross-sectional study - Adekola B. Ademoyegun; Olawale Ogundiran; Adepoju J. Kayode; Adedayo O. Olaosun; Taofeek O. Awotidebe; Chidozie E. Mbada (Heliyon, 2024)
Background: The impact of hearing loss in stroke is less explored. This study aimed to compare hearing loss in patients with sub-acute stroke with healthy controls and evaluate its association with gait and balance impairments and falls. Methods: This study involved 78 ambulant sub-acute stroke patients and 78 age-sex-matched controls. Hearing loss was assessed with pure tone average, while gait and balance impairments were assessed with the Timed Up and Go test, Berg Balance Scale, Functional Gait Assessment and 10-m walk test (gait speed). Fall occurrence was evaluated by a self-report questionnaire. Results: The prevalence of hearing loss (pure tone average of >25 dB) was higher in stroke patients than in controls (64.1% vs. 35.9%; p < 0.001). The mean pure tone average of stroke patients showed a significant positive correlation with Timed Up and Go test (r = 0.357; p = 0.001) and fall occurrence (r = 0.253; p = 0.025), and a significant negative correlation with Berg Balance Scale (r = −0.299; p = 0.008) and Functional Gait Assessment (r = −0.452; p < 0.001). There was a non-significant negative correlation with gait speed (r = −0.166; p = 0.147). Multiple regression showed that mean pure tone average was associated with Timed Up and Go test (B = 0.096; 95%CI: 0.010, 0.183) and Functional Gait Assessment (B = −0.087; 95%CI: −0.157, −0.017), but not with gait speed (B = −0.003; 95%CI: −0.007, 0.001) and Berg Balance Scale (B = −0.058; 95%CI: −0.165, 0.049). Conclusion: Hearing loss is more prevalent among patients with sub-acute stroke compared with age-sex-matched controls. Hearing loss is also associated with gait and balance impairments and falls among sub-acute stroke patients. We recommend that hearing screening and rehabilitation be incorporated into post-stroke rehabilitation programmes as part of strategies to improve balance and gait and reduce or prevent falls.